The Performance and Characterization of Polymeric Inclusion Membranes (PIMs) Containing 2-Nitro Phenyl Octyl Ether as Plasticizer on Phosphate Transport - Hanifah Nur Aini; Barlah Rumhayati; Qonitah Fardiyah; Adam Wiryawan; Ulfa Andayani; Anisah Nabilah Azzah (Syarif Hidayatullah State Islamic University, 2022)
Polymer Inclusion Membranes (PIMs) have been fabricated for diffusive passive sample layers. A study of various concentrations of plasticizers and characterization of PIM performance on phosphate transport has been carried out. The composition of PIM consisted of cellulose triacetate (CTA) as the base polymer, Aliquot 336-Cl as a carrier, and 2-Nitro phenyl octyl ether (2-NPOE) as a plasticizer. The plasticizer concentration varied between 0 and 10% (w/w). The performance of PIM on phosphate transport was studied with a passive sampler filled with 15 mL 0.1 M NaCl as the internal phase. The passive samplers were deployed into the bulk phase of a phosphate solution of 0.6 mg/L for 0-48 hours. The phosphate concentration in the passive sampler was determined using the visible spectrophotometry method at 691 nm (in the bulk phase) and 710 nm (in the internal phase). PIMs were characterized for stress-strain, contact angle, surface morphology, and cross-section. The sampling rate of phosphate, phosphate time-weighted concentration (CTWA), and accuracy of phosphate measurement was also determined. The results showed that PIM A (0% w/w 2-NPOE) resulted in a sampling rate of 0.0005±0.0002 (L/hour), CTWA 0.09 mg/L, and an accuracy of 28.38%. PIMs B (10% w/w 2-NPOE) resulted in a sampling rate of 0.0003±0.0001 (L/hour), CTWA 0.18 mg/L, and an accuracy of 52.15%. PIMs A and B have a contact angle of 17.02⁰ and 18.71⁰, respectively. It means that these PIMs are hydrophilic membranes. In addition, PIMs B was more elastic than PIMs A, showed by the tensile strength of PIMs B was 31.05 MPa compared with PIMs A's tensile strength (29.01 MPa). PIMs A and B have no pores, as shown by surface morphology using SEM. However, based on the cross-section area, PIMs A showed a break section instead of PIMs B, which indicates that PIMs B is more elastic than PIMs A.